The Book of Jonah in the context of the literary activity of the epoch of its creation - FERENC, Krzysztof (Studia Teologiczne Białystok Drohiczyn Łomża, 2021)
This paper attempts to look at the book of Jonah, a highly controversial text, especially in the past, in the context of the literary activity of the time of its composition. The book is generally considered to be a post-exilic text. As a result of the reforms of Ezra and Nehemiah, the Jews wanted to live „separated from others by the wall of the Law”. A look at the literary activity within this reform allows us to approach the Book of Jonah more appropriately. The exegesis of the scribes becomes an instrument of this reform. However, the reform encounters its adversaries. On the one side we have particularist tendencies, on the other, universalist movements. And the literary activity is not limited to the supporters of the reformers. There are also literary voices against the political-religious means of this reform. Within the group of opposition to the reform are those who know the Law and can use textual exegesis. These opponents give birth to a competing exegesis, a literature of protest. The anonymous and inspired author of the book of Jonah decides to present a universalist concept of salvation. To achieve his goal, he uses a literary form well familiar and practiced in this geographical space and at this time: the midrash.